Oseltamivir plus usual care versus usual care for influenza-like illness in primary care: an open-label, pragmatic, randomised controlled trial. Issue 10217 (4th January 2020) - Butler, Christopher C; van der Velden, Alike W; Bongard, Emily; Saville, Benjamin R; Holmes, Jane; Coenen, Samuel; Cook, Johanna; Francis, Nick A; Lewis, Roger J; Godycki-Cwirko, Maciek; Llor, Carl; Chlabicz, Sławomir; et al.
Summary: Background: Antivirals are infrequently prescribed in European primary care for influenza-like illness, mostly because of perceived ineffectiveness in real world primary care and because individuals who will especially benefit have not been identified in independent trials. We aimed to determine whether adding antiviral treatment to usual primary care for patients with influenza-like illness reduces time to recovery overall and in key subgroups. Methods: We did an open-label, pragmatic, adaptive, randomised controlled trial of adding oseltamivir to usual care in patients aged 1 year and older presenting with influenza-like illness in primary care. The primary endpoint was time to recovery, defined as return to usual activities, with fever, headache, and muscle ache minor or absent. The trial was designed and powered to assess oseltamivir benefit overall and in 36 prespecified subgroups defined by age, comorbidity, previous symptom duration, and symptom severity, using a Bayesian piece-wise exponential primary analysis model. The trial is registered with the ISRCTN Registry, number ISRCTN 27908921. Findings: Between Jan 15, 2016, and April 12, 2018, we recruited 3266 participants in 15 European countries during three seasonal influenza seasons, allocated 1629 to usual care plus oseltamivir and 1637 to usual care, and ascertained the primary outcome in 1533 (94%) and 1526 (93%). 1590 (52%) of 3059 participants had PCR-confirmed influenza infection. Time to recovery was shorter in participants randomly assigned to oseltamivir (hazard ratio 1·29, 95% Bayesian credible interval [BCrI] 1·20–1·39) overall and in 30 of the 36 prespecified subgroups, with estimated hazard ratios ranging from 1·13 to 1·72. The estimated absolute mean benefit from oseltamivir was 1·02 days (95% [BCrI] 0·74–1·31) overall, and in the prespecified subgroups, ranged from 0·70 (95% BCrI 0·30–1·20) in patients younger than 12 years, with less severe symptoms, no comorbidities, and shorter previous illness duration to 3·20 (95% BCrI 1·00–5·50) in patients aged 65 years or older who had more severe illness, comorbidities, and longer previous illness duration. Regarding harms, an increased burden of vomiting or nausea was observed in the oseltamivir group. Interpretation: Primary care patients with influenza-like illness treated with oseltamivir recovered one day sooner on average than those managed by usual care alone. Older, sicker patients with comorbidities and longer previous symptom duration recovered 2–3 days sooner. Funding: European Commission's Seventh Framework Programme.